Adipocyte deletion of the oxygen-sensor PHD2 sustains elevated energy expenditure at thermoneutrality - Wang, Rongling; Gomez Salazar, Mario; Pruñonosa Cervera, Iris; Coutts, Amanda; French, Karen; Pinto, Marlene Magalhaes; Gohlke, Sabrina; García-Martín, Ruben; Blüher, Matthias; Schofield, Christopher J.; Kourtzelis, Ioannis; Stimson, Roland H.; et al. (Nature communications, 2024)
Enhancing thermogenic brown adipose tissue (BAT) function is a promising therapeutic strategy for metabolic disease. However, predominantly thermoneutral modern human living conditions deactivate BAT. We demonstrate that selective adipocyte deficiency of the oxygen-sensor HIF-prolyl hydroxylase (PHD2) gene overcomes BAT dormancy at thermoneutrality. Adipocyte-PHD2-deficient mice maintain higher energy expenditure having greater BAT thermogenic capacity. In human and murine adipocytes, a PHD inhibitor increases Ucp1 levels. In murine brown adipocytes, antagonising the major PHD2 target, hypoxia-inducible factor-(HIF)−2a abolishes Ucp1 that cannot be rescued by PHD inhibition. Mechanistically, PHD2 deficiency leads to HIF2 stabilisation and binding of HIF2 to the Ucp1 promoter, thus enhancing its expression in brown adipocytes. Serum proteomics analysis of 5457 participants in the deeply phenotyped Age, Gene and Environment Study reveal that serum PHD2 associates with increased risk of metabolic disease. Here we show that adipose-PHD2-inhibition is a therapeutic strategy for metabolic disease and identify serum PHD2 as a disease biomarker. Calorie burning is normally turned off in thermogenic brown fat at warm temperatures. Here the authors show that adipocyte oxygen sensing directly boosts brown fat calorie burning, even at warm temperatures.